Menguji Dampak Latar Belakang Pendidikan Pada Intensi Kewirausahaan Mahasiswa Menggunakan Theory of Planned Behavior - Syaputra, Andi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
By taking a Theory of Planned Behavior (TPB), this study examines the relationship between students’ entrepreneurial, attitude (AT), subjective norms (SN), and perceived behavior control (PBC). The data used in the analysis is from 150 graduate students from 12 universities in Yogyakarta. The results indicate that attitudes and perceived behavior control significantly influenced students’ entrepreneurial intentions, but not subjective norms. This study helps understand the role of a qualified educational background, namely the Master of Management in shaping entrepreneurial intentions. Finally, this study reveals the importance of examining students’ entrepreneurialism in today’s digital age.